Enhanced 3T3-L1 differentiation into adipocytes by pioglitazone pharmacological activation of peroxisome proliferator activated receptor-gamma (PPAR-gamma) - Teixeira, Catarina (2022)
Despite the primary function of pioglitazone in antidiabetic treatment, this drug is a potent inducer of PPAR-γ, a crucial receptor that is involved in adipocyte differentiation. In this work, we propose an optimized methodology to enhance the differentiation of 3T3-L1 fibroblasts into adipocytes. This process is crucial for adipocyte secretome release, which is fundamental for understanding the molecular mechanisms that are involved in obesity for in vitro studies. To achieve this, a pioglitazone dose-response assay was determined over a range varying from 0 to 10 µM. Lipid accumulation was evaluated using Oil-Red-O. The results showed that 10 µM pioglitazone enhanced differentiation and increased secretome production. This secretome was then added into two cell lines: PC3 and RAW264.7. In the PC3 cells, an increase of aggressiveness was observed in terms of viability and proliferation, with the increase of anti-inflammatory cytokines. Conversely, in RAW264.7 cells, a reduction of viability and proliferation was observed, with a decrease in the overexpression of pro-inflammatory cytokines. Overall, the present work constitutes an improved method for adipocyte secretome production that is suitable for experimental biology studies and that could help with our understanding of the molecular mechanisms underlying adiposity influence in other cells.